Anxiety, depression, and support needs of the mothers of children with cerebral palsy and determining their opinions: Mixed methods study - Sarman, Abdullah; Tuncay, Suat; Budak, Yusuf; Demirpolat, Eyyup; Bulut, Irem (Elsevier Science Inc, 2024)
Purpose: This study aimed to determine the level of anxiety, depression, support needs and opinions of mothers of children with cerebral palsy. Design and Methods: The study used a descriptive qualitative design. The population of the study consisted of children with cerebral palsy who were educated in special education centers in a province of Eastern Turkey. All participants who volunteered for the study were accepted and the study was completed with 126 mothers. Results: Caregiver mothers with male cerebral palsy patients had higher carer support needs and anxiety total mean scores. The mean scores of depression and anxiety of the mothers who were older were statistically higher. This study found that mothers of children with diseases other than cerebral palsy had statistically higher mean depression scores. The mothers of child with cerebral palsy who had a high gross motor classification score had higher mean carer support needs, depression, and anxiety total scores. Conclusions: According to the study, depression and trait anxiety were linked to greater maternal support needs. Qualitative interviews revealed that mothers experienced issues such as stigmatization and withdrawal from social activities as a result of their children's illness. Practice implications: This study shows the relationship of need for support of mothers of children with cerebral palsy and mental problems such as depression and trait anxiety. Pediatric nurses should provide emotional support to mothers and guide them towards support groups and training programs. (c) 2024 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Anxiety; Cerebral palsy; Child; Depression; Need for support